Regulating Lives : Historical Essays on the State, Society, the Individual, and the Law. - Menzies, Robert; Chunn, Dorothy E. (Vancouver : University of British Columbia Press, 2002)
This collection explores the treatment of incest in the criminal courts, racial-ethnic dimensions of alcohol regulation, public health initiatives around venereal disease, and the seizure and indoctrination of Doukhobor children, among other issues.
Intro -- Contents -- Acknowledgments -- Regulating Lives -- Introduction -- 1 'A Strange Revolution in the Manners of the Country': Aboriginal-Settler Intermarriage in Nineteenth-Century British Columbia -- 2 Control of the Insane in British Columbia, 1849- 78: Care, Cure, or Confinement? -- 3 Racializing Prohibitions: Alcohol Laws and Racial/ Ethnic Minorities in British Columbia, 1871- 1927 -- 4 Secrets and Lies: The Criminalization of Incest and the (Re) Formation of the 'Private' in British Columbia, 1890- 1940 -- 5 'Charity Is One Thing and the Administration of Justice Is Another': Law and the Politics of Familial Regulation in Early Twentieth- Century British Columbia -- 6 Regulating the 'Respectable' Classes: Venereal Disease, Gender, and Public Health Initiatives in Canada, 1914- 35 -- 7 Race, Reason, and Regulation: British Columbia's Mass Exile of Chinese 'Lunatics' aboard the Empress of Russia, 9 February 1935 -- 8 The Politics of Naming: Constructing Prostitutes and Regulating Women in Vancouver, 1939- 45 -- 9 The State, Child Snatching, and the Law: The Seizure and Indoctrination of Sons of Freedom Children in British Columbia, 1950- 60 -- Postlude -- Contributors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Social control -- British Columbia -- History -- 19th century; Social control -- British Columbia -- History -- 20th century; Law -- Social aspects -- British Columbia; British Columbia -- Social policy; British Columbia -- Social conditions -- 19th century; British Columbia -- Social conditions -- 20th century; Electronic books